A macromolecular prodrug‐type injectable polymer composed of poly(depsipeptide‐co‐lactide)‐g‐PEG for sustained release of drugs1. (19th February 2014) - Takahashi, Akihiro; Umezaki, Masaya; Yoshida, Yasuyuki; Kuzuya, Akinori; Ohya, Yuichi; Lendlein, Andreas; Behl, Marc
<x xml:space="preserve">Abstract</x> We propose a macromolecular prodrug strategy of an injectable polymer (IP) system for continuous and sustained release of water‐soluble low‐molecular‐weight drugs. A biodegradable graft copolymer‐type IP covalently immobilizing model drugs via hydrolyzable ester bonds was synthesized through the coupling reaction of poly(depsipeptide‐co‐dl‐lactide), P(DG‐dl‐LA), having reactive carboxylic acid side‐chain groups with the amino derivative of a model drug (levofloxacin [LEV]) and monomethoxy‐poly(ethylene glycol) (PEG). The solution of the obtained graft copolymer‐type IP/model drug conjugate exhibited a temperature‐responsive sol‐to‐gel transition between room temperature and body temperature in phosphate buffer solution, similar to P(GD‐dl‐LA)‐g‐PEG without LEV. The immobilization of the LEV molecule onto P(DG‐dl‐LA)‐g‐PEG did not have a significant influence on the sol‐to‐gel transition behavior, physical properties, or in vitro degradation rates of the hydrogels. The in vitro release of LEV derivatives from the P(DG‐dl‐LA)‐g‐PEG/LEV hydrogel in phosphate buffer solution was continuous for 11 weeks, which corresponded to the degradation period of the hydrogel, and slower than that from the control hydrogels prepared from P(DG‐dl‐LA)‐g‐PEG and PLGA‐b‐PEG‐b‐PLGA that physically entrapped LEV molecules. These results suggest that the covalent attachment strategy is effective in achieving sustained release of low‐molecular‐weight drugs in IP systems and can be applied to drug delivery devices for highly bioactive drugs. Copyright © 2014 John Wiley & Sons, Ltd.